Effect of extruded finger millet (Eleusine coracan L.) on textural properties and sensory acceptability of composite bread. (1st June 2016) - Patil, Sharmila S.; Rudra, Shalini G.; Varghese, Eldho; Kaur, Charanjit
Abstract: Inclusion of native millet flour in refined wheat flour negatively affects the technological, textural and sensory properties of composite breads. The present study explores the potential of extruded finger millet flour in improving the quality of composite bread. Composite doughs with extruded finger millet were significantly (p<0.05) less firm and more extensible than their counterparts with unextruded flour. Breads elaborated from extruded finger millet (BEF) had better technological properties (higher specific volume and loaf height), good texture (low hardness, high resilience, low chewiness) than breads elaborated from unextruded finger millet (BUF). Furthermore, phenolic content and antioxidant activity of BEF was significantly improved (p<0.05) in comparison with the BUF and control bread. Sensory panel showed high preference for brown colour of composite breads (BUF and BEF) over control bread. Sensory scores of BEF were significantly (p<0.05) higher than BUF, accounting for an overall high acceptability (8.5) of BEF20 (20 g/100 g substitution level) at par with control bread. Results strongly suggest that use extruded finger millet (20 g/100 g) is an effective way of enhancing phenolics, antioxidant activity, texture and sensory quality of composite bread. Highlights: Compared the effects of native and extruded finger millet in composite wheat bread. Composite breads with extruded flour showed increased loaf volume and height. Composite breads with extruded finger millet flour had soft texture. Composite bread with 20 g/100 g extruded finger millet flour was optimized.